On the structural evolution of textile grade polyacrylonitrile fibers during stabilization and carbonization: Towards the manufacture of low‐cost carbon fiber. (April 2021) - Jin, Xing; Feng, Chunfang; Creighton, Claudia; Hameed, Nishar; Parameswaranpillai, Jyotishkumar; Salim, Nisa V.
Highlights: Carbon fibers were prepared from textile grade polyacrylonitrile (PAN) fibers. A systematic investigation on the stabilization and carbonization of textile grade PAN fibers was conducted. The tensile properties of carbon fibers from textile grade PAN fibers were found to be comparable with that of commercial PAN fibers. Textile grade PAN precursor can be an indispensable candidate for low-cost carbon fiber production. Abstract: We made an attempt to produce low cost carbon fibers using textile grade polyacrylonitrile (Tex-PAN) fibers. Here, we examined fibers collected from each zone of the stabilization and carbonization furnaces and mechanical and physical properties were measured with the aim to evaluate their chemical stability and final properties. Thermal studies revealed a cyclization peak at 308 °C and an extent of reaction of 66.2% after stabilization process. The apparent crystallite size after carbonization was determined by X-ray diffraction and it was found to be smaller in Tex-PAN fibers than commercial PAN fibers. Raman spectroscopy confirmed the development of the graphitic structures within the carbon fibers produced from Tex-PAN. Interestingly, the tensile properties (3.25 GPa) of carbon fibers from Tex-PAN fibers were found to be comparable with those of commercial PAN fibers. Precursor fibers take more than half of total production cost for producing carbon fibers (CFs), Tex-PAN precursor can be an indispensable candidate for low cost CF production.